2009
DOI: 10.1002/elps.200900245
|View full text |Cite
|
Sign up to set email alerts
|

CEC: A tool for mimicking collagen–surface interactions with apolipoprotein B‐100 peptides

Abstract: Collagens I and III are involved in the formation of the extracellular matrix and presumably in the development of several diseases, such as atherosclerosis. In this study, stable collagen and collagen-decorin coatings were prepared on the inner surfaces of fused silica CEC capillaries, enabling study of the interactions between collagen and selected peptide fragments of apolipoprotein B-100 (apoB-100), the main protein of low-density lipoprotein (LDL) particles. Interactions of positive, neutral, and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For this purpose, we selected one peptide sequence of apolipoprotein B‐100 (peptide 1) and one sequence of apolipoprotein E (peptide 2). The selected peptides were also used in our earlier interaction studies with extracellular matrix components 34. The sugars were cyclic isomers of glucose, maltose and sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we selected one peptide sequence of apolipoprotein B‐100 (peptide 1) and one sequence of apolipoprotein E (peptide 2). The selected peptides were also used in our earlier interaction studies with extracellular matrix components 34. The sugars were cyclic isomers of glucose, maltose and sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the RSD values of the EOF mobilities before and after glycation were caused most probably by slight variations in collagen I coatings [25]. The data showed that the mobility augments after the glycation, and the increase is proportional to the glycation time (Table 1).…”
Section: Glycation Time (H)mentioning
confidence: 93%
“…Collagen I coating was already optimized in our earlier work [25]. Before coating, a bare fused silica capillary (L tot 38.5 cm; L det 30 cm) was preconditioned by flushing 20 min with 1 M HCl, 10 min with 0.1 M HCl, 25 min with Milli-Q water, and 5 min with BGE at pH 7.4.…”
Section: Collagen I Coatingmentioning
confidence: 99%
See 2 more Smart Citations